1989
DOI: 10.1093/infdis/160.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with HIV Infection in Uganda

Abstract: Risk factor data were collected in 1,328 inpatients and outpatients in 1987 in 15 hospitals throughout Uganda; 42% were positive for HIV antibodies by ELISA. Seropositivity was associated with urban residence, sexually transmitted diseases (STD), number of sex partners, and sex for payment or with a person with an AIDS-like illness. Homosexuality and intravenous drug abuse, recognized risk factors in western countries, were not seen as risk factors. By multivariate analysis, urban residence and sex for payment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 18 publications
3
27
2
Order By: Relevance
“…Those characteristics which were categorised as pertaining to individual behaviour were the most important in the association, both in the bi-variate and in the multi-variate analyses. Previous studies addressing behavioural characteristics as risk factors have revealed similar patlerns of associations (Hrdy, 1987;Berkley et al, 1989;Cameron et al, 1989;Wasser et al, 1989;Mhalu, 1990;Nsubuga et al, 1990;Martin et al, 1992;Chetwynd et al, 1993). The findings also show that urban residence, perceived inadequacy of knowledge and disrupted or multiple marriage were associated with HIV-I infection.…”
Section: Discussionsupporting
confidence: 67%
“…Those characteristics which were categorised as pertaining to individual behaviour were the most important in the association, both in the bi-variate and in the multi-variate analyses. Previous studies addressing behavioural characteristics as risk factors have revealed similar patlerns of associations (Hrdy, 1987;Berkley et al, 1989;Cameron et al, 1989;Wasser et al, 1989;Mhalu, 1990;Nsubuga et al, 1990;Martin et al, 1992;Chetwynd et al, 1993). The findings also show that urban residence, perceived inadequacy of knowledge and disrupted or multiple marriage were associated with HIV-I infection.…”
Section: Discussionsupporting
confidence: 67%
“…The overall syphilis seroreactivity was 39.1% (160 out of 409 women) and was linked significantly to HIV infection (p < 0.0005) [9]. This emphasizes the fact that the presence of genital ulcers or similar lesions increases the susceptibility of HIV infection as reported in many previous studies [10,11]. The pathology which takes place is the attraction and active infiltration of lymphocytes and macrophages in these lesions and ulcers which facilitate and even force the entrance of the HIV into the blood circulation [12].…”
Section: Discussionsupporting
confidence: 58%
“…As in the USA and Europe, AIDS is very uneven in distribution. Originally, it was reported from Uganda (Serwadda, Sewankambo & Carswell, 1985) as a localised, wasting 'Slim' disease, but now it has become an acute infection strongly linked with tuberculosis (Konotey-Uhulu, 1989;Berkley, Widi-Wirski & Odware, 1989;de Cock et al, 1992). Along with other STDs, AIDS is increasingly prevalent in certain cities on the international travel routes of persons who sample the local risks, and convey their own infections and risk-behaviour to local populations.…”
Section: Weakness In the Hiv Hypothesismentioning
confidence: 99%